Pandangan Mahasiswa tentang penguatan semangat kebangsaan di era globalisasi - Fidelina, Salma Aisyawa; Nugraha, Reiza Fajar; Asmara, Chrisnandito Bagus; Rayhana, Intan Muliawati; Rahman, Naisya Anindya; Ardani, Dhea Febrian; Ningsih, Sinar Hariati; Nariswari, Asti Syahda; Nuardiansyah, Fahreza Adam; Nurdian, Yudha (Journal of Health, Education, Economics, Science, and Technology, 2025)
This research investigates the strategic role of Jember University in fostering a sense of nationalism among students in the era of globalization. Higher education is considered important for maintaining nationalism amidst the rapid flow of global information and culture. With a quantitative approach, this research explores students' views about the role of universities, the challenges they face, and strategies that can be implemented. The research results show that the University of Jember has made efforts through the curriculum, student activity unit activities, and collaboration with the government. However, nationalism is hampered by the dominance of foreign culture and changes in student lifestyles. Some suggested strategies include including national values ​​in the curriculum, holding social events, and utilizing technology to foster nationalism. The aim of this research is to evaluate the role of universities in building students' national character and provide practical recommendations for increasing patriotism amidst global challenges.